A carbapenem antibiotic inhibiting a mammalian serine protease: structure of the acylaminoacyl peptidase–meropenem complex. Issue 48 (30th November 2022) - Kiss-Szemán, Anna J.; Takács, Luca; Orgován, Zoltán; Stráner, Pál; Jákli, Imre; Schlosser, Gitta; Masiulis, Simonas; Harmat, Veronika; Menyhárd, Dóra K.; Perczel, András
Abstract : The structure of porcine AAP (pAAP) in a covalently bound complex with meropenem was determined by cryo-EM to 2.1 Å resolution, showing the mammalian serine-protease inhibited by a carbapenem antibiotic. Abstract : The structure of porcine AAP (pAAP) in a covalently bound complex with meropenem was determined by cryo-EM to 2.1 Å resolution, showing the mammalian serine-protease inhibited by a carbapenem antibiotic. AAP is a modulator of the ubiquitin-proteasome degradation system and the site of a drug–drug interaction between the widely used antipsychotic, valproate and carbapenems. The active form of pAAP – a toroidal tetramer – binds four meropenem molecules covalently linked to the catalytic Ser587 of the serine-protease triad, in an acyl–enzyme state. AAP is hindered from fully processing the antibiotic by the displacement and protonation of His707 of the catalytic triad. We show that AAP is made susceptible to the association by its unusually sheltered active pockets and flexible catalytic triads, while the carbapenems possess sufficiently small substituents on their β-lactam rings to fit into the shallow substrate-specificity pocket of the enzyme.